EFEKTIVITAS PENGGUNAAN MEDIA KIT MEKANIKA UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS FISIKA PADA MATERI USAHA DAN ENERGI KELAS X SMA NEGERI 1 KANDIS - Dimas Wahyu Jati; Fakhruddin Fakhruddin; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The ability to analyze physics is one of the skills needed in today's 21st century. This study aims to determine the ability to analyze students and to determine the difference in the ability to analyze high school students using the KIT Mechanics media and not using the media in the Business and Energy material for class X SMA Negeri 1 Kandis. This type of research is a quasi-experimental design with a posttest-only control design research model. The population of this study was all students of class X IPA SMA Negeri 1 Kandis for the academic year 2020/2021, with a sample involving 30 students from each class X IPA 1 as the experimental class, and X IPA 3 as the control class. The research instrument used was in the form of post-test questions on the ability to analyze physics in the form of objective questions accompanied by reasons for the answers, totaling 20 questions. In the matter of the ability to analyze physics, there are 3 indicators, including indicators of analyzing C4, evaluating C5, and creating C6. Then the results of the research were analyzed descriptively in the form of the ability to analyze physics and inferential in the form of normality test, homogeneity test, and independent-sample t-test with the help of SPSS 25. The results showed that learning using the Mechanics KIT media was able to improve the ability to analyze physics in the Business and Energy class material. X SMA Negeri 1 Kandis. This can be seen in the average obtained in each experimental class and control class.Keywords: Mechanics KIT Media, ability to analyze physics